Labour disputes prevention mechanisms and industrial relations: A case of wood industry in Mufindi district, Tanzania - Malekela,Thomas S. (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Degree of Master of Science in Development Policy (MSc. DP) of Mzumbe University